PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR RUPIAH TERHADAP HARGA SSAHAM PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE YANG TERCATAT DI BURSA EFEK INDONESIA - Ramadani, Fitri (Manajemen Bisnis, 2016)
Thepurpose of this research is to knowthe influence of inflation,interestrates, and the exchange rate of the rupiah against the stock price. This research wasconducted on 30 companies secto rproperty and real estatelisted onthe IndonesiastockexchangePeriod 2012 ? 2014. Data analysis techniques used in research namely OLS (Ordinary Least Square)through the help of multiple software SPSS version 18.0. Research results indicate that simultaneous inflation, interest rates, the rupiah exchanger ateand effect on stock prices. Research partially indicate that inflation is not a negative and apositive effect against the stock price, while the negative effect of interest rates significantly to the stock price and the exchange rate of rupiah apositive significant effect against the stock price.